Experimental research and engineering application on bearing capacity of concrete-filled steel tube circular arch - Jun, Wang; Chuangen, Zhu; Fuli, Bo; Guangming, Xin; Yan, Liu; Bo, Wang; Guifeng, Dong; Zhaolong, Tian (Frontiers in Materials, 2023)
The bearing property and deformation failure law of the CFST circular arch were investigated in order to provide direction for the optimization of the concrete-filled steel tube (CFST) support. The flexural bearing capacity test of the 194mm×10mm CFST was performed initially in this study. It was primarily explored how bearing capacity and deformation of circular arches were affected by the slip of the arch foot and anti-bending strengthening, and the neutral layer migration rule and anti-bending strengthening mechanism of circular arches were examined. The bearing performance of the circular arch under the condition of the concentrated load of the vault and the usual uniform load of the entire span is then simulated in an orthogonal test by numerical simulation in order to extend the experimental investigation. The study demonstrates that under focused stress on the arch top or full-span normal uniform loading, the arch foot slip is the most important element impacting the CFST support's bearing capacity. In steel tubes with the same outer diameter and wall thickness, the vector span ratio has a bigger influence than anti-bending strengthening. When the span ratio is the same, the influence of the outer diameter and wall thickness are equal and outweigh the influence of bending strengthening. The circular arch with an outside diameter of 168mm, a wall thickness of 10mm, and a rise-span ratio of 0.207 has the best performance characteristics under the influence of concentrated load, and the ultimate failure mechanism is local waist drum deformation failure. Based on the aforementioned study findings, the circular CFST support's buckling deformation and drum deformation are examined, and a composite support consisting of "anchor net spray + CFST support" is directed for the north three deep track downhill of Yangcheng Coal Mine. Two failure types expose the failure mechanism and provide a technique for optimization. The support had contributed to the circular CFST arc arch's best bearing performance in the event of waist drum deformation and failure.